Jean Lafitte: Pirate-Hero of the War of 1812 - Weintraub, Aileen (New York The Rosen Publishing Group, Inc., 2002)
This book provides information about the pirate Jean Lafitte.
Keywords: Lafitte, Jean; Pirates